The Role of Bile Acids in the Neoplastic Progression of Barrett’s Esophagus – A Short Representative Overview - Jürgens, S.; Meyer, F.; Spechler, S. J.; Souza, R. (Zeitschrift für Gastroenterologie, 2012)
Barrett’s esophagus (BE) is an intestinal metaplasia of the distal esophagus in which squamous cells are replaced by a columnar epithelium. It is considered as a premalignant lesion, which can lead to esophageal adenocarcinoma, a very aggressive type of cancer, and can often be found in patients with gastro-esophageal reflux disease (GERD). In spite of the widespread use of acid-suppressing therapy with proton pump inhibitors, the incidence of adenocarcinoma has been steadily rising during the last 30 years. So, it can strongly be suggested that refluxed material other than acid might contribute to the progression of cancer within Barrett’s esophagus. Along with gastric acid, bile acids enter the esophagus during an episode of reflux, and bile acids may be important in carcinogenesis. In their refluxates, patients with GERD and BE show high concentrations of the hydrophobic bile salt deoxycholic acid (DCA), which has cytotoxic effects and is able to induce DNA damage in different cell types. Other bile acids, like the hydrophilic urodeoxycholic acid (UDCA), have been therapeutically used to treat cholestatic liver diseases and to prevent colon carcinoma. This article reviews the effects of bile acids and points out new perceptions in the progression of Barrett’s-associated carcinogenesis.
Keywords: Barrett-Ösophagus; Gallensäuren; Desoxycholsäure (DCA); Urodesoxycholsäure (UDCA)